2019
DOI: 10.1371/journal.pone.0223012
|View full text |Cite
|
Sign up to set email alerts
|

Gait can reveal sleep quality with machine learning models

Abstract: Sleep quality is an important health indicator, and the current measurements of sleep rely on questionnaires, polysomnography, etc., which are intrusive, expensive or time consuming. Therefore, a more nonintrusive, inexpensive and convenient method needs to be developed. Use of the Kinect sensor to capture one’s gait pattern can reveal whether his/her sleep quality meets the requirements. Fifty-nine healthy students without disabilities were recruited as participants. The Pittsburgh Sleep Quality Index (PSQI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 36 publications
(36 reference statements)
4
22
1
2
Order By: Relevance
“…Our findings are in line with previous studies that also show a negative association between sleep disturbances and gait performance, 41 , 42 as well as an association between lower sleep efficiency and decreased gait speed and increased gait variability under dual-task conditions. 20 Furthermore, several studies have shown that self-reported daytime sleepiness, often a sign of disturbed sleep, was associated with increased pace variability in the DT condition.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with previous studies that also show a negative association between sleep disturbances and gait performance, 41 , 42 as well as an association between lower sleep efficiency and decreased gait speed and increased gait variability under dual-task conditions. 20 Furthermore, several studies have shown that self-reported daytime sleepiness, often a sign of disturbed sleep, was associated with increased pace variability in the DT condition.…”
Section: Discussionsupporting
confidence: 93%
“… 9 , 10 Since both sleep quality and gait are major contributors to health, one could expect that they influence each other. 11 Previous evidence has highlighted, that the association between sleep quality and gait is bidirectional. 12–17 For example, a study by Goldman et al 12 has shown, that the gait speed of those who sleep less than 6 hours per night is 3.5% slower, compared to those who sleep 6–8 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, all trajectories had be normalized in some way. A basic method to standardize trajectories is to use the z-score of p (the time series of coordinates for x, y, and z): where μ is the mean value and σ is the standard deviation of p. This method has been used for motion feature normalization in classification tasks 46 , 47 . Figures 2 to 6 were normalized using this method.…”
Section: Technical Validationmentioning
confidence: 99%